Phenotypic Transition of the Collecting Duct Epithelium in Congenital Urinary Tract Obstruction. (13th December 2009) - Trnka, Peter; Hiatt, Michael J.; Ivanova, Larissa; Tarantal, Alice F.; Matsell, Douglas G.
Abstract : Epithelial-mesenchymal transition (EMT) has emerged in recent years as an important process in the development of organ fibrosis in many human diseases. Our previous experience in a nonhuman primate model of obstructive nephropathy suggested that EMT of collecting duct epithelium contributes to the development of interstitial fibrosis. In this study we demonstrate for the first time in humans that obstructed fetal collecting duct epithelium undergoes transition to mesenchymal phenotype, characterized by decreased expression of epithelial markers, de novo expression of mesenchymal markers with subsequent loss of cell-cell interaction, disruption of the basement membrane, and increased deposition of extracellular matrix into the expanded interstitium of the obstructed kidney. The results of this study therefore support the previous findings from animal studies and suggest that EMT of the collecting duct epithelium might contribute to the development of interstitial fibrosis in human fetal obstructive nephropathy.